THE STUDY OF PECULIARITIES OF SOCIAL SELF-CONTROL AND COPING BEHAVIOUR - Karapetyan, N.I. (Արդի հոգեբանություն, 2025)
This article is devoted to the analysis of the peculiarities of the manifestation of coping behavior of the employee in the manager-employee relationship. А pilot study was conducted тo reveal the practical side of these issues, in which 23-65 year old experienced people were participated with a working experience of 3-15. It reveals the relationship of social self-control and coping behavior of employees in the dependency of work experience and age peculiarities.